2019
DOI: 10.1111/tid.13142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of infectious risk and outcomes in the hmong renal transplant population

Abstract: Background: Hmong ethnicity has been associated with infection, particularly fungal.The risk of infection after transplant in the Hmong population is unknown.Methods: Observational study of adult renal transplant (RTX) recipients between 1/1/1994 and 12/31/2015. Primary objective was to identify infectious risk in the Hmong RTX population as compared to non-Hispanic whites (NHW). Secondary objective was to evaluate transplant outcomes. Results:There was a total of 2599 patients in the study window; 95 Hmong, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Pneumonia has been reported in 80% of kidney transplant with blastomycoses, and disseminated disease commonly includes cutaneous manifestations (82). Risk for blastomycosis in kidney transplant is difficult to assess outside of environmental exposure given the relatively infrequent events; one study from Wisconsin identified two of three cases developed in a minority population, the Hmong (87). Similar to histoplasmosis, diagnosis focuses on direct visualization or culture from sputum, BAL, or tissue.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Pneumonia has been reported in 80% of kidney transplant with blastomycoses, and disseminated disease commonly includes cutaneous manifestations (82). Risk for blastomycosis in kidney transplant is difficult to assess outside of environmental exposure given the relatively infrequent events; one study from Wisconsin identified two of three cases developed in a minority population, the Hmong (87). Similar to histoplasmosis, diagnosis focuses on direct visualization or culture from sputum, BAL, or tissue.…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Jorgenson et al 12 compared the rates of infections between Hmong and non-Hispanic White KTRs during the first-year post-transplant and found that BK infection (6.7% vs. 9.1%, p = .84) was less frequent in Hmong patients although the difference was not statistically significant. In contrast to our study, Hmong patients were selected based on ethnic group but not separated into foreign versus US-born.…”
Section: Number Of Infectious Complicationsmentioning
confidence: 99%
“…However, this expanded screening for these latent infections is not standardized and may be potentially insufficient for early detection and appropriate management of RIM patients. Although previous studies in pediatric and adult RIM kidney transplant recipients (KTRs) have demonstrated similar outcomes of graft function and mortality compared to US‐born KTRs (USKTR), none of these studies have reported detailed information about the type and timing of infectious episodes 3,12–15 . More granular data could guide and improve the prevention, diagnostics, and treatment of post‐transplant infections, especially for foreign‐born KTRs (FBKTR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation